2018
DOI: 10.2147/ijn.s152571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zirconium oxide nanoparticles addition on the optical and tensile properties of polymethyl methacrylate denture base material

Abstract: Background Polymethyl methacrylate (PMMA) is widely used for the fabrication of removable prostheses. Recently, zirconium oxide nanoparticles (nano-ZrO 2 ) have been added to improve some properties of PMMA, but their effect on the optical properties and tensile strength are neglected. Objective The aim of this study was to investigate the effect of nano-ZrO 2 addition on the translucency and tensile strength of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 46 publications
(68 reference statements)
10
129
0
1
Order By: Relevance
“…The results of the current study showed that the addition of NZ increased the tensile strength of PMMA/NZ composite. This outcome is in agreement with previous studies confirming the positive effect of NZ addition to PMMA denture base material where it had a direct relation with flexural, impact, and tensile strengths (11,24,26) . The increase in tensile strength could be linked to a good dispersion of the NZ fillers within the matrix, and due to their nano-size, they have the capability of filling the matrix interstitially and improving the strength thereafter.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the current study showed that the addition of NZ increased the tensile strength of PMMA/NZ composite. This outcome is in agreement with previous studies confirming the positive effect of NZ addition to PMMA denture base material where it had a direct relation with flexural, impact, and tensile strengths (11,24,26) . The increase in tensile strength could be linked to a good dispersion of the NZ fillers within the matrix, and due to their nano-size, they have the capability of filling the matrix interstitially and improving the strength thereafter.…”
Section: Discussionsupporting
confidence: 93%
“…The value of tensile strength was computed using the following formula: TS=F/A, Where, TS = Tensile strength (N/mm 2 ), F = Force at failure (N), A = Area of a cross section at failure (mm 2 ). Testing procedures were performed at 23° C and 50% relative humidity (24) .…”
Section: Conducting Tensile Strength Testmentioning
confidence: 99%
“…Several ceramic powders are used as reinforcement for PMMA, e.g. barium titanate, zirconium oxide, alumina and hydroxyapatite (HA) [2,6,7]. The biodegradation, osteoconduction, osteointegration and biocompatibility of the HA is the promise behind the used of HA reinforcement material for biomedical application.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement in the tensile strength of the denture base acrylic was directly proportional to the nano-ZrO 2 concentration while PMMA translucency declined when nano-ZrO 2 concentration was increased. 121 Sarraf et al built a hybrid biofunctionalized coating encompassing nano-tubular rows of titanium dioxide (TiO 2 NTs) with decorated silver oxide NPs (Ag 2 O NPs) on their edges in order to improve the biological behaviors and anti-bacterial activities of Ti 6 Al 4 V implants ( Fig. 3).…”
Section: Nano-materials For Edentulismmentioning
confidence: 99%